Junction Temperature Estimation of SiC MOSFETs in Three-Level NPC Inverters - Lee, In Ho; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2024)
This paper presents a junction temperature estimation method of silicon carbide (SiC) metal–oxide–semiconductor field-effect transistors (MOSFETs) in three-level neutral point clamped (NPC) inverters. The thermal characteristic of power switches is an essential part that affects the reliability of power conversion systems such as three-level NPC inverters. The power loss of MOSFET devices is derived from both the electrical properties of the device and the current conducted through the device. The generated power loss during the operation of inverters is dissipated in the form of thermal energy. Therefore, the junction temperature caused by the power loss is calculated using a thermal model. The proposed method analyzes the dynamic characteristics of temperature variation using instantaneous values such as voltage, current, on-resistance, and parasitic capacitance. The thermal model reflects the characteristics of each inner layer constituting the MOSFET using an RC Cauer network, representing the heat transfer through multiple layers of a power device. The effectiveness of this estimation method was verified using simulation and experimental results.
Keywords: Junction temperatures; Metaloxide semiconductor field-effect transistor (MOSFETs); Neutral-point clamped inverters; Powerloss; RC cauer network; Silicon carbide metal–oxide–semiconductor field-effect transistor; Temperature estimation; Thermal model; Three-level neutral point clamped; Three-level neutral point clamped inverte; Junction temperature; Power loss; RC Cauer network; SiC MOSFET; Thermal model; Three-level NPC inverter